Kreativitas Mahasiswa Calon Guru Dalam Pemecahan Masalah Matematika Ditinjau Dari Gaya Berpikir - Anwar, Muhammad (APOTEMA : Jurnal Program Studi Pendidikan Matematika, 2018)
This research study aims to describe the creativity of student teachers in solving mathematical problems in terms of the average difference between the style of thinking Monarchic, hierarchic, oligarchic and Anarchic. Creativity is referred to in this research is the process and the products ability to think students or activities geared to produce something new. Mathematical problems referred to in this study are math problems that are not immediately be resolved using certain rules are already known by the students. The subjects were students who think Monarchic style, hierarchic, oligarchic or Anarchic. To choose a subject of study, students were asked to fill questionnaire instrument thinking styles used as guidelines in determining the thinking styles of students. Based on the results sheet instruments stuffing on the thinking styles, students are grouped according to the style of thinking and thinking style groups each have 1 (one) students as research subjects. After that, the selected students were given a math problem solving test and be interviewed. From the results of tests and interviews, the researchers identified the creativity in each subject of study. To make the data valid student activity results then triangulation at different times. Once the data is valid, then the researchers analyzed and concluded creativity of student teachers in solving mathematical problems in terms of thinking styles. The results of this study, it was found that 1) the creativity of students who have a thinking style monarchic (SM) in solving mathematical problems not meet the criteria of creativity in this study. 2) Creativity of students who have a thinking style Hierarchy (SH) in solving mathematical problems meeting the criteria of creativity that fluency and flexibility. 3) Creativity of students who have a thinking style oligarchic (SO) in solving mathematical problems not meet the criteria of creativity in this study. 4) Creativity of students who have a thinking style Anarchic (SA) to solve mathematical problems not meet the criteria of creativity in this study.